Answer:
x=26
Explanation:
We can use the Pythagorean theorem for this answer.
Pythagorean Theorem: a^2 +b^2 = c^2
We can see that both triangles are right triangles. We should first find the hypotonus of the bottom triangle.
So, we plug in the values.
6^2 +8^2 = c^2
36 +64 = c^2
c^2= 100
c= square root of 100
c=10
The hypotonus for the bottom triangle is equivalent to the base of the top triangle. Therefore, we can use the Pythagorean Theorem again.
10^2 +24^2= c^2
100+576+c^2
c^2 = 676
c= square root of 676
c= 26
The answer to the problem is 26.